The spring-mass model and the energy cost of treadmill running - Dalleau, G.; Belli, A.; Bourdin, M.; Lacour, J.-R. (European Journal of Applied Physiology, 1998)
During running, the behaviour of the support leg was studied by modelling the runner using an oscillating system composed of a spring (the leg) and of a mass (the body mass). It was concluded that the spring-mass model is a good approach further to understand mechanisms underlying the interindividual differences in Cr (energy cost of running).